Relationship between Malay Language Writing Skills and Learning Motivation among Non-Native Speakers - Said, Rozita Radhiah; Nahar, Nor’azian; Kiram, Norazlina Mohd (International Journal of Academic Research in Progressive Education and Development, 2019)
The study was carried out to determine the relationship between Malay language (BM) writing skills and learning motivation among non-native speakers. A total of 414 research participants from 5 Chinese National-type primary schools (SJKC) and Tamil National-type primary schools (SJKT) in the district of Kuantan were selected for the study. Two instruments were developed which were a questionnaire to gauge learner motivation and a writing skill proficiency test for BM at primary school level (UPBM_SR). The study adopted a cross-sectional research design. Data was analysed using IBMSPSS version 23. Results from the writing test show that a majority of respondents achieved Level 1 (Very Minimal) at 25.1% (104 respondents), followed by Level 3 (Limited) at 20.3% (84 respondents), Level 2 (Minimal) at 19.8% (82 respondents), Level 4 (Fairly Skilful) at 14.5% (60 respondents), Level 5 (Almost Skilful) at 10.1% (42 respondents), Level 6 (Skilful) at 7.2% (30 respondents), and Level 7 (Skilful) at 2.9% (12 respondents). No respondents achieved Level 8 (Highly Skilful). The mean score for instrumental learning motivation was significant with r (412) = 0.22, p<.001 and the mean score for integrative learning motivation was also significant with r (412) = 0.18, p<.001. Based on Cohen’s (1998) interpretation, the relationship shown is small. Results of the linear regression (β=.20, p<.01) show that writing ability is not the main factor affecting the overall score of UPBM_SR. It is hoped that the findings of the study could enhance the knowledge of BM teachers in National-type schools across Malaysia. It is also hoped that the UPBM_SR instrument could be used to develop the BM proficiency of non-native speakers in primary schools in preparation for writing tests at higher levels of schooling.